2013
DOI: 10.1177/0363546513488866
|View full text |Cite
|
Sign up to set email alerts
|

Posterolateral Corner Reconstruction Using the Single Fibular Sling Method for Posterolateral Rotatory Instability of the Knee

Abstract: Anatomic PLC reconstruction using a single fibular sling method is an effective and relatively simple procedure for most patients with posterolateral rotatory instability, with the exception of those with severe multiple injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
4
16
0
1
Order By: Relevance
“…This low failure rate is to be highlighted, especially as treatment of posterolateral lesion was not homogeneous, except for being systematically surgical. This good control of both components of posterolateral instability despite differing reconstruction techniques is borne out by the literature: e.g., Yang et al [25] using the Larson technique, and Tardy et al [26] using anatomic reconstruction. It is, thus, not possible to conclude in favor of anatomic reconstruction, in agreement with Thaunat et al [27].…”
Section: Discussionmentioning
confidence: 99%
“…This low failure rate is to be highlighted, especially as treatment of posterolateral lesion was not homogeneous, except for being systematically surgical. This good control of both components of posterolateral instability despite differing reconstruction techniques is borne out by the literature: e.g., Yang et al [25] using the Larson technique, and Tardy et al [26] using anatomic reconstruction. It is, thus, not possible to conclude in favor of anatomic reconstruction, in agreement with Thaunat et al [27].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical indications for them were more than grade II PCL injuries with or without more than grade II PLC injuries. 16,58 The inclusion criteria were (1) a minimum follow-up period of 2 years, (2) 8-mm increased posterior tibial translation compared with that of the uninvolved knee on posterior stress radiography, 17,21 (3) a difference of .10°between knees on the dial test at 30°and 90°w ith a 5-mm increase in the varus gap compared with the uninvolved knee on varus stress radiography in cases of combined PLRI, 34,39,58 (4) transtibial PCL reconstruction with remnant preservation using a transposterior septal portal, and (5) PLC reconstruction using the single fibular sling method in cases of combined PLRI. We excluded patients with (1) bilateral injuries, (2) multiple ligament injuries except for a combined PCL and PLC injury, (3) use of other PCL or PLC reconstruction techniques, (4) combined lower extremity fractures, (5) infections, (6) revision surgery, (7) more than grade 3 cartilage lesions as assessed by the Outerbridge classification system, (8) varus or valgus malalignment in a lower extremity, and (9) prior surgery on the involved knee.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The single fibular sling for PLC reconstruction was created as described previously ( Figure 1). 8,49,58 Two femoral tunnels were created just proximal to the anatomic insertion sites of the popliteal tendon and fibular collateral ligament. The fibular collateral ligament attaches slightly proximal (1.4 mm) and posterior (3.1 mm) to the lateral epicondyle, and the popliteal tendon attachment is about 18.5 mm anterior to it.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Correlation with Tegner activity scores was 0.56 in one study, suggesting measurement of a separate activity-related construct 28. In other studies, postoperative IKDC scores corresponded with Lysholm, Cincinnati, KOOS, and Orthopädische Arbeitsgruppe Knie (OAK) scores 9–12 15 16 19 21 24 25 27–49. However, these studies did not detail individual patient scores, and thus, correlations with the IKDC could not be quantified.…”
Section: Resultsmentioning
confidence: 87%
“…Four studies demonstrated no difference in postoperative scores in patients treated with isolated PLC reconstruction versus those treated with combined PLC/cruciate ligament reconstruction 9 21 24 25. Similarly, there was no difference in postoperative scores in patients treated with isolated PCL versus those treated with combined PCL/other ligament reconstructions 26 27.…”
Section: Resultsmentioning
confidence: 98%